Evolutionary mechanisms shaping the genetic population structure of coastal fish: insight from populations of Coilia nasus in Northwestern Pacific. (December 2014) - Gao, Tianxiang; Wan, Zhenzhen; Song, Na; Zhang, Xiumei; Han, Zhiqiang
Abstract A number of evolutionary mechanisms have been suggested for generating significant genetic structuring among marine fish populations in Northwestern Pacific. We used mtDNA control region to assess the factors in shaping the genetic structure of Japanese grenadier anchovy, Coilia nasus, an anadromous and estuarine coastal species, in Northwestern Pacific. Sixty seven individuals from four locations in Northwestern Pacific were sequenced for mitochondrial control region, detecting 61 haplotypes. The length of amplified control region varied from 677 to 754 bp. This length variability was due to the presence of varying numbers of a 38-bp tandemly repeated sequence. Two distinct lineages were detected, which might have diverged during Pleistocene low sea levels. There were strong differences in the geographical distribution of the two lineages. Analyses of molecular variance and the population statistic ΦST revealed significant genetic structure between China and Ariake Bay populations. Based on the frequency distribution of tandem repeat units, significant genetic differentiation was also detected between China and Ariake Bay populations. Isolation by distance seems to be the main factor driving present genetic structuring of C. nasus populations, indicating coastal dispersal pattern in this coastal species. Such an evolutionary process agrees well with some of the biological features characterizing this species